Normal form approach to some chaotic sprott systems - İldeş, Medine. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
In this study, the normal form method which had been previously applied to three of the Sprott systems is applied to three other Sprott systems with a different eigenvalue structure of their linearized parts. It is seen that the normal form expansion can also represent these systems successfully for a longer time than expected from a perturbative method. Altough the normal form expansion is a local method it gives information about nonlocal characteristics suh as possible zero Liapunov exponents of the system via approximately conserved quantities.
Keywords: Chaotic behavior in systems.